Pengembangan Panduan Konseling Individual Cognitive Behavior dengan Teknik Cognitive-Restructuring untuk Meningkatkan Penerimaan Diri Siswa SMK - Ananda, Safira Nur Aziza; Ramli, M; Utami, Nugraheni Warih (citeus, 2025)
Self-acceptance is an aspect that is needed by students, especially in self-actualization. This study aims to produce a product in the form of an individual cognitive behaviour counseling guide for cognitive restructuring techniques to increase the self-acceptance of students at state vocational high schools who meet the acceptance criteria, which include usability, accuracy, convenience, and attractiveness. The research was conducted using the Research and Development approach developed by Borg and Gall. The subjects in this study were two Guidance and Counseling lecturers as material expert tests, two Education Technology study program lecturers as media experts, and two school counselors as potential users. The results of the validation data for material experts, media experts, and potential users were analyzed using an inter-rater agreement. Based on the results of validation data analysis, this guide obtains a rater agreement index of 1.00 from each validation of material experts, media experts, and potential users. The results of the guide validation analysis entered the very high rater agreement category. It can be concluded that the development of individual cognitive behaviour counseling guidelines for cognitive restructuring techniques to increase student self-acceptance has fulfilled the product acceptance criteria, which include four aspects, namely aspects of usability, accuracy, convenience, and attractiveness, and this guide is very feasible to use.